Taxonomic account and phylogenetic relationships of the species of the Neotropical social wasp genus Chartergus Lepeletier, 1836 (Vespidae: Polistinae: Epiponini) - Somavilla, Alexandre; Aragão, Marcos; Barroso, Paulo Cézar Salgado; Carpenter, James M.; Menezes, Rodolpho Santos Telles (Zootaxa, 2024)
The Neotropical social wasp genus Chartergus is reviewed and comparative diagnoses, images of type material, and an updated identification key for species are presented. To investigate the phylogenetic relationships within the genus, we used a combined dataset of morphological characters, nest architecture traits, and molecular data. The results revealed the following relationships among the Chartergus species: (C. globiventris + (C. artifex + C. metanotalis)).